Nada Šabec, 2021: Slovene Immigrants and Their Descendants in North America: Faces of Identity - Sicherl, Eva (Slavia Centralis, 2022)
Prispevek predstavlja znanstveno monografijo Nade Šabec Slovene Immigrants and Their Descendants in North America: Faces of Identity (2021).